Effect of Service Administration System Electronic Passport (E-Passport) Towards Community Trust and Satisfaction - Rifai, Rifai (Riviera Publishing, 2022)
Introduction: This study examines the influence of the electronic passport service administration system (e-passport) on public trust and satisfaction. Based on previous studies, the latest of this study is in the addition of trust and public satisfaction variables in the electronic passport (e-passport) service administration system. Method: This study falls under the category of descriptive quantitative research. This research was conducted on consumers making electronic passports (E-passports) in the West Nusa Tenggara area. The sampling technique in this study was simple random sampling with a research sample of 100 respondents. The data analysis technique in this study was Partial Least Square (PLS). Result: It explores how the perception of the ease of e-passport service affects public trust, the ease of service e-passport affects public satisfaction, the practicality of e-passport service affects public trust, the expediency of e-passport services affects public satisfaction, public trust affects public satisfaction, public trust can mediate the perception of ease of e-passport service towards public satisfaction, community trust can mediate the perception of the practicality of e-passport services to public satisfaction. Conclusion: the perception of specific and valuable e-passport services can increase public satisfaction and trust.